2010
DOI: 10.1002/mc.20614
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced expression of cancer testis antigen genes in glioma stem cells

Abstract: Cancer stem cells are an important target for effective therapy, since they show tumorigenicity, chemoresistance, and radioresistance. We isolated cancer stem cells from glioma cell lines and tissues and examined the expression of cancer testis antigen (CTA) genes as potential target molecules for cancer vaccine therapy. CTA genes were highly and frequently expressed in cancer stem cells compared with differentiated cells. In addition, histone acetylation levels in the promoter regions of CTA genes were high i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
26
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 35 publications
4
26
0
Order By: Relevance
“…Finally, CTA expression has been reported in cancer stem cells, among others in melanoma and glioma. 47,48 In MM, a putative cancer stem cell has been reported, and may be CD19+CD138-ve. 49,51 The putative importance of CTA genes in these cells is subject to future investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, CTA expression has been reported in cancer stem cells, among others in melanoma and glioma. 47,48 In MM, a putative cancer stem cell has been reported, and may be CD19+CD138-ve. 49,51 The putative importance of CTA genes in these cells is subject to future investigation.…”
Section: Discussionmentioning
confidence: 99%
“…CD133 expression has been suggested as a marker of stemness in this malignancy based on the observation that CD133 positive cells can give rise to tumorigenic cells [58,59].…”
Section: Cancer Testis Antigensmentioning
confidence: 99%
“…Interestingly, CTAs such as LAGE-1, NY-ESO-1 and MAGE family members are also expressed in GBM CD133 positive cells, compared with differentiated or parent cells [59].…”
Section: Cancer Testis Antigensmentioning
confidence: 99%
See 1 more Smart Citation
“…This may point to the widespread expression of BORIS which is not restricted to cancerous cell lines. In addition, it has been found that the expression of some CT genes does not rely on the presence of BORIS [12,17,48,49], and thus, it is unlikely that BORIS would be a major CT gene inducing factor [50]. Furthermore, some more general biological functions including a regulatory role in normal cell division have been proposed for BORIS [47], which leads to a significant decrease in cell proliferation and clonogenic capacity.…”
Section: Introductionmentioning
confidence: 99%